Influence of geometrical characteristics of sidewall-type multiple aneurysms on hemodynamic factors. (25th June 2015) - Hua, Yufeng; Kim, Yong Bae; Oh, Je Hoon
Multiple aneurysms occur rarely and have not been well investigated. The purpose of this study is to verify whether high rupture risk of multiple aneurysms is due to the interaction between multiple aneurysms' geometrical characteristics. The following geometrical characteristics were varied in an idealized sidewall-type model: aneurysm a 1 's dome-neck length ( S ), size ratio, inflow angle ( α ), distance between two aneurysms ( D ), and the parent vessel's angle ( θ ). We varied the parent blood vessel and aneurysm sac a 1 's geometrical characteristics to analyze their hemodynamic influence on aneurysm a 2 . By comparing the influence on aneurysm a 2, we found that parent blood vessel geometrical characteristics such as the distance between aneurysms ( D ) and the parent vessel's angle ( θ ) were the most hemodynamically influential characteristics examined. The impact of varying the aneurysm's geometrical characteristics such as dome-neck length ( S ), size ratio, and inflow angle ( α ) was not obvious. The reason for the higher rupture rate of multiple aneurysms is not due to interactions between the aneurysm sacs but due to factors of each individual aneurysm.